Evaluation of knowledge & awareness of medical students on HIV/AIDS before and after teaching curriculum - M. Bharathi; B. Naga Srilatha; Sasidhar M.; Sasikala A. (International Journal of Medical Research and Review, 2015)
Introduction: The HIV/AIDS pandemic has become one of the most important public health problems in recent times. India has the 3rd highest number of estimated people living with HIV/AIDS (PLHA) in the world. It is an urgent necessity that the doctors of tomorrow are prepared to deal with the many outcomes of the spread of HIV infection in the community. WHO strongly recommends the incorporation of knowledge of HIV/AIDS in medical syllabus starting from the 1styear.Methods: A Prospective study was conducted to assess the knowledge and awareness of medical students and effectiveness of curriculum on HIV/AIDS at RIMS Medical College, Kadapa, Andhra Pradesh in July and September 2015. 150 students of 4th semester were included after taking their consent. A questionnaire having 30 items of closed ended except three and subjective items were administered. Base line knowledge was assessed by pretest evaluation. Post-test evaluation was done two months after teaching curriculum for two hours.Results: The knowledge of students after teaching curriculum regarding HIV/AIDS was high in all aspects when compared to pre intervention.Conclusions: Awareness of students on HIV/AIDS was improved in post-intervention assessment.1. Few students (11/150) only knew about p 24 antigen. 2. Students’ knowledge about vertical transmission and non-modes of transmission of HIV still needs intervention. 3. Regarding vulnerable groups, symptoms and testing strategies – their awareness was poor.